2016
DOI: 10.1016/j.heliyon.2016.e00218
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and techno-functionality of flours and proteins from two edible insect species: Meal worm ( Tenebrio molitor ) and black soldier fly ( Hermetia illucens ) larvae

Abstract: Depending on the species, edible insects are highly nutritious and thus represent a noteworthy alternative food and feed source. The current work investigates the protein extractability and techno-functionality of insect flour fractions recovered from Tenebrio molitor and Hermetia illucens. T. molitor and H. illucens flours contained about 20% crude fat and 60% and 36 % crude protein, respectively. Defatting reduced the crude fat content to 2.8% (T. molitor) and 8.8% (H. illucens) and increased the crude prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
198
12
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(245 citation statements)
references
References 36 publications
30
198
12
5
Order By: Relevance
“…The isoelectric point (IP) was found to be located at pH 4 (data not shown). These results are in accordance with studies reporting considerable low solubility of insect protein flours derived from mealworm larvae (3-45%; pH 2-9), black soldier fly larvae (10-35%; pH 2-9), house cricket (12-23%, pH 3-9) and tropical banded cricket (5-25%; pH 3-10), especially at weak acidic conditions [20,23,33]. In contrast, Azagoh et al [22] observed higher protein solubility of flour from mealworm larvae between 40-76% from pH 2-10.…”
Section: Protein Solubilitysupporting
confidence: 92%
See 3 more Smart Citations
“…The isoelectric point (IP) was found to be located at pH 4 (data not shown). These results are in accordance with studies reporting considerable low solubility of insect protein flours derived from mealworm larvae (3-45%; pH 2-9), black soldier fly larvae (10-35%; pH 2-9), house cricket (12-23%, pH 3-9) and tropical banded cricket (5-25%; pH 3-10), especially at weak acidic conditions [20,23,33]. In contrast, Azagoh et al [22] observed higher protein solubility of flour from mealworm larvae between 40-76% from pH 2-10.…”
Section: Protein Solubilitysupporting
confidence: 92%
“…Similar observations of enhanced oil binding properties were reported for globulin-based rapeseed isolate and soy protein isolate after enzymatic hydrolysis [30,51]. The general degree of oil binding found for the hydrolysed and non-hydrolysed MLPF significantly surpasses the OBC of different flours and protein fractions of mealworm and black soldier fly larvae ranging between 0.4 and 0.9 g Oil /g DM [20].…”
Section: Water and Oil Binding Capacitysupporting
confidence: 82%
See 2 more Smart Citations
“…The protein quality in terms of essential amino acid content satisfies the recommendation for adult`s requirement by the WHO [6]. First, studies on techno-functional properties of TML protein fractions revealed promising protein solubilities between 60 and 100% at alkaline pH depending on the applied pre-treatment, extraction procedure and fractions' composition [14][15][16][17].…”
Section: Introductionmentioning
confidence: 84%